EVALUASI PAJAK SEBAGAI KEBIJAKAN FISKAL NEGARA MODERN DALAM PERSPEKTIF MAQASHID SYARIAH - Ferdian Al Ghifari Ganda Hutama; Ai Siti Farida (ADISAM PUBLISHER, 2026)
Tax serves as a central fiscal instrument in modern states; however, among Muslim societies it frequently raises debates concerning its normative legitimacy and conformity with Sharia principles, particularly due to its distinction from zakat and the Baitul Mal system. This study seeks to assess taxation as a fiscal policy instrument through the Maqashid Sharia framework by examining the extent to which tax policies contribute to the realization of substantive public welfare within a modern state context. A qualitative research design is employed, combining a systematic literature review with in-depth interviews involving academics, taxation practitioners, and university students. The collected data are analyzed using thematic analysis grounded in the five core dimensions of Maqashid Sharia: hifz ad-din, hifz an-nafs, hifz al-aql, hifz an-nasl, and hifz al-mal. The results reveal that taxation demonstrates significant potential to align with Maqashid Sharia, particularly in safeguarding human well-being, ensuring generational continuity, and maintaining collective wealth stability through the provision of public goods and services. Nonetheless, limitations persist in the realization of hifz al-aql and hifz al-mal, primarily due to regulatory complexity, limited tax literacy, and unequal benefit distribution. These findings underscore the necessity of enhancing governance quality, transparency, and the systematic incorporation of Maqashid Sharia principles in tax policy evaluation to strengthen fiscal legitimacy within Muslim communities